Permanent discontinuation of different anticoagulants in patients with atrial fibrillation and the impact on clinical outcome: data from the GARFIELD-AF registry. (25th November 2020) - Cools, F; Johnson, D; Pieper, K.S; Camm, A.J; Bassand, J.-P; Fitzmaurice, D.A; Fox, K.A.A; Goldhaber, S.Z; Goto, S; Haas, S; Turpie, A.G.G; Verheugt, F.W.A; et al.
Abstract: Background: Non-Vitamin K Antagonists (NOAC) are replacing vitamin K Antagonists (VKA) as first line oral anticoagulant therapy (OAC) in patients with non-valvular atrial fibrillation (NVAF). Discontinuation of OAC might put patients at increased risk. It was anticipated that patients who were on NOAC would discontinue OAC less. Purpose: We compare the rates and impact on outcome of the discontinuation of NOAC and VKA using data from the GARFIELD-AF registry. Methods: Patients included in GARFIELD-AF, had a new diagnosis of NVAF and at least 1 stroke risk factor. In this analysis 26, 299 patients (VKA: 13, 012; NOAC: 13, 287) that received OAC were included. Permanent discontinuation was defined as stopping OAC for at least 7 consecutive days (whether or not restarted during follow-up). Marginal structural Cox proportional hazards models estimated the effect of discontinuation on death, cardiovascular (CV) death, non-haemorrhagic stroke + systemic embolism (NHS+SE), myocardial infarction (MI), or combined endpoints. Adjustments were made for both baseline factors and time dependent variables. Results: Of all patients, 15.6% discontinued OAC (VKA: 15.4%; NOAC: 15.8%) over a median follow-up of 181 days (IQR: 359). Most discontinued early (67.0% of patients on VKA and 47.1% of patients on NOAC ≤4 months). Significantly higher discontinuation risk was seen with worsening kidney function, coronary artery disease, history of bleeding (baseline factors), as well as with all types of bleeding (time dependent factors). Lower discontinuation rates were seen with history of stroke/TIA, hypertension, increasing age, permanent AF (all p<0.01). Mean CHA2DS2-VASc score was 3 in all groups. Patients in both treatment arms who discontinued were at increased risk for death, NHS+SE, MI as well as combined endpoints of death/NHS+SE/MI, death/NHS+SE and a trend towards higher CV death (Figure 1). All interaction tests for the interaction of treatment and discontinuation had a p value >0.4. The association between discontinuation and outcomes did not change when a 30 day discontinuation window was used. Conclusion: The rate of discontinuation in this study was 15.8% and comparable for VKA and NOAC over a 2-year follow-up. Discontinuation rates were the highest soon after the initiation of treatment. When VKA or NOAC was stopped for ≥7 consecutive days, the risk of NHS+SE, death, MI or any combined endpoints were significantly worse in both treatment arms. These data suggest that discontinuation of anticoagulant treatment with VKA or NOAC should be discouraged. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): The GARFIELD-AF registry is funded by an unrestricted research grant from Bayer AG.